Pengaruh Terapi Musik Jazz Terhadap Kualitas Tidur Pada Siswa Kelas XII SMK Bunga Persada Cianjur - Arista Alifia (Universitas Katolik Widya Karya Malang, 2023)
Introduction : Sleep quality is a person getting enough sleep is characterized by not being easily tired, not irritable, restless, lethargic, headaches and not easily drowsy. The purpose : of this study was to analyze the effect of jazz music therapy on sleep quality. Method : This type of research used the Pre-Experimental method with the One Group Pre-Post Test Design approach, the sample in this study was 18 respondents, using the Purposive Sampling technique and the data collection method used the PSQI sheet. Result : The test used was the Wilcoxon Sign Rank with p 0.05. The results showed that before jazz music therapy the average sleep quality in the sleep quality category was quite bad, reaching 61.1%, whereas after jazz music therapy there was an increase in good sleep quality. Conclution : This is proven based on the Wilcoxon test data processing with the result (p = 0.001) that there is an effect of jazz music therapy on students. The results of the study are expected that giving jazz music therapy can be further developed as an intervention to improve the quality of good sleep in students.